2004
DOI: 10.1093/nar/gkh305
|View full text |Cite
|
Sign up to set email alerts
|

5'-Untranslated regions with multiple upstream AUG codons can support low-level translation via leaky scanning and reinitiation

Abstract: Upstream AUGs (uAUGs) and upstream open reading frames (uORFs) are common features of mRNAs that encode regulatory proteins and have been shown to profoundly influence translation of the main ORF. In this study, we employed a series of artificial 5'-untranslated regions (5'-UTRs) containing one or more uAUGs/uORFs to systematically assess translation initiation at the main AUG by leaky scanning and reinitiation mechanisms. Constructs containing either one or two uAUGs in varying contexts but without an in-fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 41 publications
3
131
0
1
Order By: Relevance
“…Abundant evidence supports the role of uORFs as translational regulators, exerting this function through their engagement of ribosomes [61][62][63], inferring this is the main, canonical function of uORFs. Similarly, it has been suggested that smORFs within LncRNAs, or overlapping annotated coding mRNAs, could function mainly as regulators of transcript stability, by engaging the non-sense mediated decay (NMD) pathway [64][65] .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Abundant evidence supports the role of uORFs as translational regulators, exerting this function through their engagement of ribosomes [61][62][63], inferring this is the main, canonical function of uORFs. Similarly, it has been suggested that smORFs within LncRNAs, or overlapping annotated coding mRNAs, could function mainly as regulators of transcript stability, by engaging the non-sense mediated decay (NMD) pathway [64][65] .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…We have shown that translation at the CFTR pAUG codon occurs at 15% of wildtype levels in the context of the CFTR -132 5´UTR. A number of possible mechanisms could result in the failure of scanning small rRNA subunits to recognise and initiate translation at the c.-34C>T uAUG in the CFTR -132 5´UTR and continue scanning, termed 'leaky' scanning [Wang and Rothnagel, 2004]. Such small rRNA subunits may continue scanning and then recognise the CFTR pAUG and initiate translation of the protein coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Upstream AUGs not in frame with the start codon may lead to leaky scanning (Kozak 1989a, b) and reinitiation of translation, resulting in inefficient translation of mRNAs (Wang and Rothnagel 2004). When the first and second start codons are in different reading frames, leaky scanning enables one mRNA to produce two completely different proteins.…”
Section: Start Codon Context Of Rice and Arabidopsis 5-utrsmentioning
confidence: 99%